The Price of Experience - Jeong, Hyeok; Kim, Yong; Manovskii, Iourii (American Economic Review, 2015)
We identify a key role of factor supply, driven by demographic changes, in shaping several empirical regularities that are a focus of active research in macro and labor economics. In particular, demographic changes alone can account for the large movements of the return to experience over the last four decades, for the differential dynamics of the age premium across education groups emphasized by Katz and Murphy (1992), for the differential dynamics of the college premium across age groups emphasized by Card and Lemieux (2001), and for the changes in cross-sectional and cohort-based life-cycle profiles emphasized by Kambourov and Manovskii (2005). (JEL D91, E24, I23, J11, J24, J31)